2021
DOI: 10.1002/jcv2.12029
|View full text |Cite
|
Sign up to set email alerts
|

Neurostructural correlates of retinal microvascular caliber in adolescent bipolar disorder

Abstract: Objectives Vascular‐brain associations are well established in adults but neglected in youth and psychiatric populations, who are at greater cardiovascular risk. We therefore examined the association of retinal vascular caliber with regional brain structure in adolescents with and without bipolar disorder (BD). Methods One hundred and three adolescents (n = 51 BD, n = 52 healthy control [HC]) completed retinal fundus imaging, yielding arteriolar and venular diameters, followed by T1‐weighted 3‐Tesla MRI. Regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…By demonstrating coronary microvascular dysfunction in youth early in their course of BD, independent of obesity and medications, the current study adds important preliminary evidence that microvessels may be implicated in the excess and premature onset of CVD in BD. There is a small but growing body of literature showing that microvascular dysfunction is present in BD and has psychiatric clinical correlates (Fiedorowicz, Coryell, Rice, Warren, & Haynes, 2012;Kennedy et al, 2023aKennedy et al, , 2023bMio et al, 2021;Urback, Metcalfe, Korczak, MacIntosh, & Goldstein, 2019). While BD is listed as a tier II moderate-risk condition for future CVD by the American Heart Association (Goldstein et al, 2015a) While additional research is needed to change future clinical practices, it is possible that, in the future, microvascular metrics may guide prevention and treatment strategies, and inform more personalized CVD risk assessment among individuals with BD and other illnesses characterized by microvascular dysfunction.…”
Section: Potential Clinical Applications and Generalizability Of Find...mentioning
confidence: 99%
“…By demonstrating coronary microvascular dysfunction in youth early in their course of BD, independent of obesity and medications, the current study adds important preliminary evidence that microvessels may be implicated in the excess and premature onset of CVD in BD. There is a small but growing body of literature showing that microvascular dysfunction is present in BD and has psychiatric clinical correlates (Fiedorowicz, Coryell, Rice, Warren, & Haynes, 2012;Kennedy et al, 2023aKennedy et al, , 2023bMio et al, 2021;Urback, Metcalfe, Korczak, MacIntosh, & Goldstein, 2019). While BD is listed as a tier II moderate-risk condition for future CVD by the American Heart Association (Goldstein et al, 2015a) While additional research is needed to change future clinical practices, it is possible that, in the future, microvascular metrics may guide prevention and treatment strategies, and inform more personalized CVD risk assessment among individuals with BD and other illnesses characterized by microvascular dysfunction.…”
Section: Potential Clinical Applications and Generalizability Of Find...mentioning
confidence: 99%
“…The studies published in the special issue contribute to further our understanding on the links between Attention-Deficit/Hyperactivity Disorder (ADHD) and asthma (Sun et al, 2021); the relationship between anorexia nervosa and inflammatory bowel diseases (Larsen et al, 2021); the association of retinal vascular calibre with regional brain structure in adolescent bipolar disorder (Mio et al, 2021); the role of integrated care for child and adolescent health (Fazel et al, 2021); the acceptability, feasibility and impact of a drop-in centre to address emotional and behavioural problems in children with chronic physical conditions (Bennett et al, 2021); the efficacy of group-based Acceptance and Commitment Therapy for adolescents with multiple functional somatic syndromes (Kallesøe et al, 2021); and the evidence on physical exercise interventions in child and adolescent mental health (Carney & Firth, 2021). These studies add to and complement, with more fine-grained information, an increasing body of empirical evidence on the relationships between mental disorders and physical conditions in children and adolescents.…”
mentioning
confidence: 99%
“…These studies add to and complement, with more fine‐grained information, an increasing body of empirical evidence on the relationships between mental disorders and physical conditions in children and adolescents. Indeed, for some associations in adults or in children/adolescents (e.g., ADHD and asthma [Cortese et al., 2018 ], ADHD and obesity [Cortese et al., 2016 ], depression and diabetes [Graham et al., 2020 ]) meta‐analytic synthesis is available. We are therefore at a point now where it is possible to provide high‐level, quantitative evidence synthesis of this body of evidence.…”
mentioning
confidence: 99%
“…For example, one study found no difference in two measures of retinal vessel diameter when comparing a BPD group to an HC group (Naiberg et al, 2017). However, another study (Mio et al, 2021) with a larger sample size found a significantly larger average retinal arteriolar diameter in BPD patients compared to HCs, but not in retinal venular diameter. In two studies comparing an MDD with type II diabetes group, a type II diabetes only group, and an HC group, significant differences in retinal vessel measurements were found between the MDD group and the HC group, but not between the MDD group and the diabetes group (Nguyen et al, 2008(Nguyen et al, , 2010.…”
Section: Structural Retinal Correlates Of Neuropsychiatric Disordersmentioning
confidence: 99%